In-vessel co-composting of yard waste and food waste: an approach for sustainable waste management in Cameron Highlands, Malaysia - Malakahmad, A. (Springer Berlin Heidelberg, 2017)
Purpose: Huge amount of yard waste is produced in cities with excessive agricultural activities like Cameron Highlands, Malaysia where most of the time the yard waste is being managed poorly and big portion of it ends in dump sites. Therefore, this study aims to evaluate the applicability of converting yard waste generated in Cameron Highlands Malaysia into high-quality and fast compost via in-vessel method. Methods: In-vessel composting technique was applied for speedy biotransformation of yard waste. Addition of food waste, effective microorganisms (EM) and Shimamoto Enzyme® (SE) were investigated for improvement of compost quality. Four compositions of feedstock with different yard waste (YW) and food waste (FW) ratios were tested. The compositions were 70YW + 30FW, 80YW + 20FW, 90YW + 10FW and 100YW. Physicochemical properties of compost including pH, moisture content and C/N ratio were monitored throughout the experiment. Furthermore, quality of compost and its potential for direct application after production were evaluated based on germination index (GI) and nutrient content (NPK). Results: The compost samples had pH ranging from 7 to 9 and moisture content of 15.45–32.13. Initial C/N ratio of all feedstock was decreased throughout the composting process by more than 50. Seed germination test showed that only 70YW + 30FW feedstock produced immature compost with GI < 80. The highest GI of 130 was obtained when FW represented in 10 of the feedstock with addition of EM. Average concentrations of nitrogen, phosphorus and potassium were 1.73, 1.21 and 1.66 in case of EM additive and 1.47, 0.56 and 1.74 in case of SE additive. Conclusion: Application of in-vessel composting can improve solid waste management in Cameron Highlands, Malaysia and yield a high-demand product. The approach used in this study can be a good practice for the societies have difficulties in managing their yard waste. © 2017, The Author(s).